The Selection of Project Construction Method to Achieve the OTOBOSOROR Goal at Blue Ammonia Project - Hermawan Yudhistiro; Utomo Sarjono Putro (Green Publisher Indonesia, 2026)
PT. Kilang Pertamina Internasional (PT KPI) is mandated to support the Government's Strategic Program on the Green Economy Pioneer through the development of the Blue Ammonia Plant project, which must be executed in accordance with the OTOBOSOROR target (On Time, On Budget, On Specification, On Regulation, and On Return). One of the most critical milestones in project implementation is the selection of the Project Construction Method, a complex decision influenced by multiple internal and external factors. This research evaluated construction methods Stick Built, Modularization, Pre-Assembly Unit (PSU), and their combination using an integrated SWOT Analysis and Analytic Hierarchy Process (AHP) methodology. The OTOBOSOROR target is translated into SWOT factors to formulate strategies that leverage Strengths, address Weaknesses, capitalize on Opportunities, and mitigate Threats. In the AHP framework, SWOT factors are ranked through pairwise comparisons, systematically converting the Project Team's qualitative judgments into a numerical basis for decision-making. The results identified the four most influential parameters in selecting the construction method: Manpower availability and expertise (18.38%), Support from Government (13.20%), Proven experience in mega project operations (11.93%), and Technology maturity (7.21%). Furthermore, the optimal construction method is the combination of Stick-Built, Modularization, and Pre-Assembly Unit (PSU), with the results demonstrating robustness across varying criteria weights in sensitivity analysis. These findings provide a strategic framework for PT KPI to achieve the OTOBOSOROR objectives while accommodating internal capabilities and external environmental conditions.